SOCIAL INTEGRATION OF MOLDOVAN MIGRANT’S CHILDREN IN ITALY - Deleu, Ecaterina (Economy and Sociology, 2023)
The article explores the features of the Moldovan migrant’s children integration in Italy and the dynamics and particularities of the second-generation formation. The study is based on statistical data analysis on the Moldovan communities of immigrants in Italy and the integration of migrant children into educational institutions. The risk factors of social adaptation of children of Moldovan migrants based on the sociological quantitative and qualitative research conducted in 2015-2019 are analyzed. The study results show that the children of Moldovan migrants face difficulties integrating into Italian society, even though they have more opportunities than their parents. There are specific differences in children’s integration depending on the age of arrival in Italy, the success in learning the Italian language, the type of family (full or single parent, mixed family), and the intensity of social contacts. Children of migrants born in Italy do not experience significant difficulties in social integration, primarily thanks to their knowledge of the Italian language. Children from mixed families where one of the parents is an Italian citizen also do not have a problem. The most significant difficulties are encountered by young people who arrived in Italy as teenagers and have lived in Moldova for a long time with other relatives since their parents moved abroad for work. The need to reunite with the family after 5-10 years of separation from parents, sometimes with a new mixt family, creates additional psychological and sociocultural barriers in the process of integrating children in Italy.